Armies and Ecosystems in Premodern Europe The Meuse Region, 1250-1850 - Govaerts, Sander (War and Conflict in Premodern Societies, 2021)
Military history; Ecological history; war and the environment; Natural barriers in history; wildlife protection, mosasaur; premodern environmentalism